Saikokaryukotsuboreito during pregnancy protects rat neonates from maternal cannibalism and death in a neurolathyrism experimental model. Issue 2 (October 2016) - Kusama‐Eguchi, Kuniko; Kawaguchi, Kimino; Yakubo, Syuji; Kitanaka, Susumu; Matsuzaki, Keiichi; Takamiya, Tomoko; Fukuda, Noboru; Masuko, Takashi; Hirose, Dai; Makino, Mitsuko; Ueda, Yukiko; Ikegami, Fumio; et al.
ABSTRACT: Aim: Stress during the perinatal period may result in failure to thrive in the newborn. A possible preventive effect of two kampo formulae, saikokaryukotsuboreito (SRB) and hachimijiogan (HJG) on the incidence of hind‐leg paraparesis and mortality in newborns, including that due to maternal cannibalism, were examined in neurotoxin‐treated rats. Methods: Female Wistar/ST rats treated with SRB or HJG during pregnancy and the lactation period were separated from their pups for 6 h daily and then reunited. The pups were treated daily with a neurotoxin, l ‐β‐ N ‐oxalyl‐α, β‐diaminopropionic acid (l ‐β‐ODAP), to cause neurolathyrism‐like symptoms, a motor defect leading to hind‐leg paraparesis. Results: Although SRB and HJG treatment in mother rats did not affect the incidence of motor defect (paraparesis) in the pups, pup mortality was greatly and significantly decreased during the treatment period in the SRB group but not in the HJG group. Conclusion: SRB treatment in mother rats is effective in decreasing pup mortality mainly due to cannibalism, thus suggesting its potential for anxiety disorder during the perinatal period in humans.